Technologies for silvopastoral Monitoring and Assessment - Hassan, Sawsan; Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2024)
The presentation highlights the innovative application of technology in evaluating and monitoring the health and productivity of silvopastoral systems. A key tool discussed is Vegmeasure, a software that utilizes image analysis to accurately assess vegetation cover and biomass. This presentation, delivered by Sawsan Hassan and Mounir Louhaichi during the group training course on 'Mapping and Inventorying Semi-Arid Silvopastoral Systems,' was held at the ICARDA office in Tunis from May 7 to 10, 2024.